Novel plasma protein binding analysis method for a PET tracer and its radiometabolites: A case study with [11C]SMW139 to explain the high uptake of radiometabolites in mouse brain - Aarnio Richard; Alzghool Obada M; Wahlroos Saara; O'Brien-Brown James; Kassiou Michael; Solin Olof; Rinne Juha O; Forsback Sarita; Haaparanta-Solin Merja (Netherlands, 2025)
Radiometabolites of PET tracers interfere with imaging and need to be taken into account when modeling PET data. Various tracer and radiometabolite characteristics affect the uptake rate into tissue. In this study, we investigated two such factors, lipophilicity and protein-free fraction. A novel rapid method was developed using thin-layer chromatography with digital autoradiography (radioTLC) and ultrafiltration for analyzing the protein-free fractions of an exemplar PET tracer, [11C]SMW139 (fP, free parent tracer over all radioactivity), and its radiometabolites (fM, free radiometabolites over all radioactivity). Detailed understanding of the uptake of radiometabolites into extravascular cells requires analyzing fM, which has not previously been performed for PET tracers. Mice were injected with [11C]SMW139, and time-activity curves from plasma and brain coupled with the parent fraction and free fraction data were analyzed to demonstrate the true levels of protein-free and protein-bound [11C]SMW139 and its radiometabolites in plasma. The ultrafiltration method included separate membrane correction factors for the parent tracer and its radiometabolites for analysis of unbiased fP and fM. Metabolism of [11C]SMW139 was rapid, and after 45 min, the parent fraction was 0.33 in plasma and 0.28 in brain. Ultrafiltration membrane correction had a significant effect on the fP but not the fM. From 10-45 min, the fP decreased from 0.032 to 0.007, while fM remained between 0.52 and 0.35. The much higher fM in plasma could explain why the less lipophilic radiometabolites enter the brain efficiently. This detailed understanding of fP and fM from rodents can be used in translational studies to explain the behavior of the tracer in humans. Similar parent fraction and plasma protein binding methods can be used for human in vivo analysis.